EXPLORING FINANCIAL COST CONTROL STRATEGIES AT VANKE - Thompson, Sarah (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
The shareholding structure of Vanke, a prominent real estate company, exhibits notable stability, with Shenzhen Metro Group Co. Ltd. emerging as the leading shareholder, holding a substantial 27.9% stake